Transcutaneous Electrical Nerve Stimulation: A Review of Dental Applications - Pandita, Vaibhav; Ajila, Vidya; Babu, G. Subhas; Hegde, Shruthi; Asan, Mohamed Faizal (Journal of Health and Allied Sciences NU, 2021)
Transcutaneous electrical nerve stimulation or TENS is a nonpharmacologic method that is used to alleviate pain from various acute and chronic conditions. TENS works through activation of descending inhibitory neurons of the central nervous system. In dentistry, TENS has applications for pain reduction in temporomandibular disorders and postherpetic neuralgia. It has also been studied for its role in increasing salivary secretion in subjects with xerostomia and as a local anesthetic agent in pediatric dentistry. Its wide applications in the orofacial region make it an important treatment modality. The purpose of the present review was to describe the general principles and its applications in dentistry along with its indications, advantages, and disadvantages. A web-based search was conducted using the keywords “transcutaneous electrical nerve stimulation,” “temporomandibular joint,” “TENS,” “TMJ,” “orofacial pain,” and “Management.” The manuscripts thus obtained were evaluated and used for compiling the present narrative review. The present review focuses on the mechanism of action, applications, and effectiveness of TENS in the management of diseases of the maxillofacial region.
Keywords: transcutaneous electrical nerve stimulation; TENS; temporomandibular joint; pain